(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Road traffic accidents are considered one of the important general health concerns, as they result in numerous injuries and deaths worldwide. India is a developing nation which experiences very high rate of such accidents. This study was planned to study the sociodemographic profile of victims of fatal RTAs involving different types of vehicles, so as to widen the database for developing the preventive measures that could reduce morbidity and mortality in such cases. A retrospective study was conducted on one hundred cases of road traffic accidents brought for medicolegal autopsy to mortuary of Pt. B.D Sharma PGIMS Rohtak over a period of one year. Their age, gender, region and other socioeconomic factors were studied.